2012
DOI: 10.2967/jnumed.111.097352
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Amino Acid PET–Guided Surgery for Supratentorial High-Grade Gliomas

Abstract: High-grade gliomas are brain tumors associated with a devastating prognosis. Recent studies have indicated that the combined use of amino acid PET and MRI is superior to MRI alone to plan the surgical resection of high-grade gliomas. The aim of the study was to analyze the cost-effectiveness of the use of amino acid PET for the surgical resection of high-grade gliomas, compared with MRI alone, from the perspective of the national health insurance in Germany. Methods: A decision-tree model was set up to compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…Moreover, our results are also in line with other cost-effectiveness analyses evaluating the use of amino acid PET in patients with newly diagnosed gliomas (23,27). The results of these studies suggested that amino acid PET might be cost-effective for planning the surgical resection of rHGG and for selecting the biopsy site for newly diagnosed brain tumors.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, our results are also in line with other cost-effectiveness analyses evaluating the use of amino acid PET in patients with newly diagnosed gliomas (23,27). The results of these studies suggested that amino acid PET might be cost-effective for planning the surgical resection of rHGG and for selecting the biopsy site for newly diagnosed brain tumors.…”
Section: Discussionsupporting
confidence: 88%
“…For the attribution of probability distributions to the variables of the decision tree, triangular distributions were used (23,(26)(27)(28). On the basis of the initial definition of the intervals by the experts, we fitted the respective distributions for all variables (Table 2).…”
Section: Sensitivity Analysesmentioning
confidence: 99%
“…Models such as the one presented by the authors are important tools to summarize the available data and, based on this, to draw conclusions on the medical effectiveness and cost-effectiveness of the procedure in question. This has already been performed for several other nuclear medicine procedures [16][17][18]. Wale et al deliver additional information that goes well beyond the known literature.…”
mentioning
confidence: 83%
“…The inclusion of more true negative cases would also help to better determine the specificity, although this could be difficult, as patients may not necessarily undergo biopsy if FET-PET is negative. Finally, although cost-effectiveness of FET-PET in the management of patients with brain tumor has recently been studied, the results obtained should be treated with caution due to several limitations of the reported model [45,46]. Thus, there is still a need for cost-effectiveness studies of FET-PET, used separately or in combination with MRI, in the clinical setting.…”
Section: Study Characteristicsmentioning
confidence: 99%